Comparison of Efficiency of Closed Kinetic Chain Exercises Versus Proprioceptive Exercises in Improving Balance and Gait in People With Hemophilia: Protocol for a Randomized Controlled Trial - Poyraz Isleyen, Tugce; Tarakci, Ela; Leblebici, Gokce; Yeldan, Ipek; Zulfikar, Bulent (JMIR research protocols, 2025)
Inherited bleeding disorders involve prolonged bleeding due to clotting protein deficiencies, with hemophilia A and B being the most common types. The severity of bleeding in people with hemophilia depends on the deficient factor level. Treatment includes coagulation factor concentrates, nonreplacement preparations, gene therapies, and physiotherapy, whereby bleeding is prevented, symptoms are reduced, and the quality of life is improved. Closed kinetic chain exercises improve joint stability and neuromuscular control by stabilizing the proximal base, making them favored in musculoskeletal rehabilitation. Proprioceptive exercise training improves the sensorimotor system's adaptability and injury prevention through tailored programs involving progressively complex movements and surfaces. The aim of this study is to investigate the effects of closed kinetic chain exercises and proprioceptive exercise training on improving balance and walking in people with hemophilia. This study is a 3-arm, parallel-group randomized controlled trial with 63 people with hemophilia aged 13-25 years who meet the inclusion criteria. The primary outcome measures are medio-lateral swing, anterior-posterior swing, walking speed, and Hemophilia Joint Health Score. Secondary outcome measures are kinematic assessment of gait, one-leg stand test, 6-minute walk distance (6MWD) test, proprioception assessment, and the Functional Independence Score in Hemophilia. Participants will be evaluated with the Biodex balance system for postural sway, 10-meters walking test for gait speed, Hemophilia Joint Health Score for joint health, Kinovea 2D motion analysis for kinematic evaluation of gait, one-leg stand test for balance measurement, 6MWD for functional capacity, digital goniometer for proprioception, and Functional Independence Score in Hemophilia for functional independence. Participants will be randomly assigned to a closed kinetic chain exercise group, a proprioceptive exercise group, or a control group. All participants in exercise training groups will receive a 30-minute education session on joint protection techniques and energy conservation prior to the first exercise session. Closed kinetic chain exercises will include progressive lower limb exercises of approximately 45 minutes each session. Proprioceptive exercise training will focus on vibration training; reposition exercises and proprioception exercises will be administered to increase proprioceptive input for the same duration as the other group. The control group will receive no intervention. All participants will undergo 24 exercise sessions (2 days a week for 12 weeks). After the treatment, the initial measurements will be repeated. This study began in September 2023 and is scheduled to be completed in May 2025. A total of 34 participants have completed the study to date. This study will investigate the effects of 2 different exercises on functional parameters in people with hemophilia. The effects of different exercise protocols on parameters such as postural sway, walking speed, and joint health will be evaluated. It is predicted that both exercise methods may have positive effects on balance and gait. Clinical Trials.gov NCT05879549; https://clinicaltrials.gov/study/NCT05879549. DERR1-10.2196/66770.